Structure and Growth Control of Organic–Inorganic Halide Perovskites for Optoelectronics: From Polycrystalline Films to Single Crystals. Issue 4 (15th March 2016) - Chen, Yani; He, Minhong; Peng, Jiajun; Sun, Yong; Liang, Ziqi
Abstract : Recently, organic–inorganic halide perovskites have sparked tremendous research interest because of their ground‐breaking photovoltaic performance. The crystallization process and crystal shape of perovskites have striking impacts on their optoelectronic properties. Polycrystalline films and single crystals are two main forms of perovskites. Currently, perovskite thin films have been under intensive investigation while studies of perovskite single crystals are just in their infancy. This review article is concentrated upon the control of perovskite structures and growth, which are intimately correlated for improvements of not only solar cells but also light‐emitting diodes, lasers, and photodetectors. We begin with the survey of the film formation process of perovskites including deposition methods and morphological optimization avenues. Strategies such as the use of additives, thermal annealing, solvent annealing, atmospheric control, and solvent engineering have been successfully employed to yield high‐quality perovskite films. Next, we turn to summarize the shape evolution of perovskites single crystals from three‐dimensional large sized single crystals, two‐dimensional nanoplates, one‐dimensional nanowires, to zero‐dimensional quantum dots. Siginificant functions of perovskites single crystals are highlighted, which benefit fundamental studies of intrinsic photophysics. Then, the growth mechanisms of the previously mentioned perovskite crystals are unveiled. Lastly, perspectives for structure and growth control of perovskites are outlined towards high‐performance (opto)electronic devices. Abstract : The development of structures and growth of organic–inorganic halide perovskites in forms of polycrystalline films and single crystals is reviewed, which is directed towards the optimization of their optoelectronic performance. A key is to implement a fine control of film morphology and crystal growth of perovskites.